2023
DOI: 10.3390/cryst13050829
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on (n,n)-Nanotubes Rolled-up from B/N Substituted Me-Graphene

Abstract: In this work, the n,n-type nanotube systems rolled up from the B/N substituted Me-graphene (i.e., Me-CBNT and Me-CNN, respectively) were investigated with the aid of the density functional theory (DFT). Due to the lattice dynamic instabilities until n=10, the n,0 and n,m nanotube systems were not involved in this study. According to our calculations at the Perdew-Burke-Ernzerhof (PBE) level, the n,n Me-CBNT and Me-CNNT systems possess excellent mechanical strengths. The Young’s moduli of Me-CBNTs can reach 60%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Yin et al found that changes in the geometry and hybridization ratio of OSMs lead to significant changes in the morphology and grain boundaries of OSM/SWCNT composite films, which in turn affect the thermoelectric properties of the films [ 32 , 33 , 34 , 35 ]. In addition, theoretical study on OSM/SWCNT composites is helpful as in the case of using density-functional theory (DFT) on the investigation of electronic configuration of ( n , n )-nanotubes by Jia’s group [ 36 ]. Some research progress has been made on OSM/SWCNT composites, but as it is, they still lag behind polymer/SWCNT composites and inorganic thermoelectric materials.…”
Section: Introductionmentioning
confidence: 99%
“…Yin et al found that changes in the geometry and hybridization ratio of OSMs lead to significant changes in the morphology and grain boundaries of OSM/SWCNT composite films, which in turn affect the thermoelectric properties of the films [ 32 , 33 , 34 , 35 ]. In addition, theoretical study on OSM/SWCNT composites is helpful as in the case of using density-functional theory (DFT) on the investigation of electronic configuration of ( n , n )-nanotubes by Jia’s group [ 36 ]. Some research progress has been made on OSM/SWCNT composites, but as it is, they still lag behind polymer/SWCNT composites and inorganic thermoelectric materials.…”
Section: Introductionmentioning
confidence: 99%